Framework para compartilhamento do conhecimento em equipes multidisciplinares que usam metodologia ágil no desenvolvimento de produtos digitais - Santos, Leticia Gomes dos (2022)
To respond to changes in the business environment, successful organizations need to develop new products that generate specific value for a group of people, customers, and users. Knowledge Sharing is the key to this, considering that products are built through individual and organizational knowledge. Multidisciplinary teams have gained ground in the development of products, mainly software, through agile methodologies. Knowledge sharing occurs in teams through moments and mechanisms, therefore, it is important to identify them. Product development requires effective knowledge sharing, as it has the cooperation of people from different parts of the organization with different knowledge and experience levels. If knowledge sharing does not occur effectively, there is a high probability that the delivery of the product will be different from what was requested. The aim of this study is to propose a framework for Knowledge Sharing in multidisciplinary teams that use agile methodology in the digital product development. To this end, a qualitative study was developed in which ten interviews were conducted and eighteen meeting observations were performed. The results found in the analysis of interviews and observations led to the identification of the moments, mechanisms, barriers and facilitators for Knowledge Sharing in the digital product development. They also allowed the construction of the framework and the elaboration of propositions, which help to improve Knowledge Sharing. As the main academic and managerial contribution, the Knowledge Sharing framework is presented during the Sprint.